A modified urinary catheterisation technique to reduce urine leakage: A prospective randomised study. (29th July 2021) - Jia, Limin; Lin, Yulian; Qian, Weiyang; Yang, Guihong; Zhang, Chenguang; Fu, Xin; Feng, Jing; Wang, Lihua; Zhu, Hong; Fan, Lili; Chen, Xiaoyun
Abstract: Background: Long‐term indwelling catheters assist people who are unable to use another bladder management method. However, urine leakage is a common problem with an indwelling urinary catheter. This study aims to determine whether a modified catheterisation technique would reduce urine leakage incidence. Methods: Participants were randomly divided into conventional or modified catheterisation groups. In the modified technique group, the volume of fluid that needed to be injected into the balloon to obtain a suitable catheter front‐end curvature (120–145°) was measured before catheterisation. Baseline characteristics and first‐time success rates and procedure durations were similar between groups. Results: There were 30 patients in each group. Compared with conventional catheterisation, the modified catheterisation group had smaller residual urine volume (median 11 mL Vs. 30.5 mL, p <0.001) and more leakage‐free days (30 days Vs. 10 days, p <0.001). Leakage‐free survival was longer in the modified catheterisation group ( p <0.001). The residual urine volume (>17 vs ≤17 ml (median); incident rate ratio (IRR), 28.710; 95%CI, 4.114–200.331; p =0.001) was independently associated with urine leakage. Conclusions: The modified catheterisation technique may reduce the incidence of urine leakage.